2015
DOI: 10.1371/journal.pone.0119422
|View full text |Cite|
|
Sign up to set email alerts
|

Membrane-Active Macromolecules Resensitize NDM-1 Gram-Negative Clinical Isolates to Tetracycline Antibiotics

Abstract: Gram-negative ‘superbugs’ such as New Delhi metallo-beta-lactamase-1 (bla NDM-1) producing pathogens have become world’s major public health threats. Development of molecular strategies that can rehabilitate the ‘old antibiotics’ and halt the antibiotic resistance is a promising approach to target them. We report membrane-active macromolecules (MAMs) that restore the antibacterial efficacy (enhancement by >80-1250 fold) of tetracycline antibiotics towards bla NDM-1 Klebsiella pneumonia and bla NDM-1 Escherichi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 30 publications
2
55
0
Order By: Relevance
“…We found that the macromolecules restored the efficacy of existing antibiotics to as low as 0.1 μg mL -1 ( S2 and S3 Tables). Using the fractional inhibitory concentration (FIC = [X]/MIC X , where [X] is the lowest inhibitory concentration of compound 1 in the presence of the compound 2), a combination was called synergistic when the FIC index (FICI = FIC compound1 + FIC compound2 ) was ≤ 0.5 [ 34 ]. Both the molecules showed synergistic profiles with erythromycin and rifampicin against E .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the macromolecules restored the efficacy of existing antibiotics to as low as 0.1 μg mL -1 ( S2 and S3 Tables). Using the fractional inhibitory concentration (FIC = [X]/MIC X , where [X] is the lowest inhibitory concentration of compound 1 in the presence of the compound 2), a combination was called synergistic when the FIC index (FICI = FIC compound1 + FIC compound2 ) was ≤ 0.5 [ 34 ]. Both the molecules showed synergistic profiles with erythromycin and rifampicin against E .…”
Section: Resultsmentioning
confidence: 99%
“…baumannii (FICI in the range of 0.1–0.5) ( S2 Table ). Unlike erythromycin and rifampicin that are inherently resistant, Gram-negative bacteria acquire resistance to tetracycline antibiotics and we have recently reported that these cationic macromolecules resensitized planktonic cells of NDM-1 producing Gram-negative clinical isolates to tetracycline antibiotics [ 34 ]. These results suggested that this class of macromolecules have the potential to restore the efficacy of established antibiotics.…”
Section: Resultsmentioning
confidence: 99%
“…Macromolecules. Membrane-active macromolecules (MAMs) have been found to enhance the uptake of tetracycline by bacterial cells and therefore are able to resensitize NDM-positive strains to tetracycline (309). The MAM-tetracycline combination was bactericidal, in contrast to the bacteriostatic effect of tetracycline alone (309).…”
Section: Antimicrobial Adjuvants In Developmentmentioning
confidence: 99%
“…However, colistin has uncertain efficacy in pulmonary infections, and its use has always been hampered by the occurrence of renal toxicity, and to a lesser extent, neurological adverse effects. [ 49 50 72 74 75 76 77 78 ] More importantly, carbapenem resistant bacteria such as blaNDM-1 E. coli and blaNDM-1 K. pneumoniae have become resistant to colistin. [ 77 ] Tigecycline is a glycylcycline with a wide spectrum of activity against aerobic and anaerobic Gram-positive and Gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%